Lodewijk De Smet. (22nd July 2022) - Green, Suzanne; Kirton, Roxane; Martin, David; Hobgen, Keith; de Brauwere, Nic; Gibson, Richard
Abstract: His dedication and commitment to animal welfare set him apart from the rest. Never afraid to call out poor welfare, he always took an independent view and was scrupulously fair.